John Marshall Harlan : great dissenter of the Warren Court - Yarbrough, Tinsley E., 1941- (OUP E-Books., 1992)
John Marshall Harlan served on the Supreme Court from 1955 until his retirement and death in 1971. An articulate and forceful critic of the expansive civil liberties doctrines and constitutional trends of the period, Harlan is considered one of the most scholarly jurists ever to have served on the Supreme Court. This is the first book-length biography and analysis of his judicial and constitutional philosophy.